Development of a Digital RT-PCR Method for Absolute Quantification of Bluetongue Virus in Field Samples - Rocchigiani, Angela M.; Tilocca, Maria G.; Portanti, Ottavio; Vodret, Bruna; Bechere, Roberto; Di Domenico, Marco; Savini, Giovanni; Lorusso, Alessio; Puggioni, Giantonella (Frontiers in Veterinary Science, 2020)
Bluetongue (BT) is a major Office International des Epizooties (OIE)-listed disease of wild and domestic ruminants caused by several serotypes of Bluetongue virus (BTV), a virus with a segmented dsRNA genome belonging to the family Reoviridae, genus Orbivirus. BTV is transmitted through the bites of Culicoides midges. The aim of this study was to develop a new method for quantification of BTV Seg-10 by droplet digital RT-PCR (RTdd-PCR), using nucleic acids purified from complex matrices such as blood, tissues, and midges, that notoriously contain strong PCR inhibitors. First, RTdd-PCR was optimized by using RNAs purified from serially 10-fold dilutions of a BTV-1 isolate (105.43TCID50/ml up to 10−0.57 TCID50/ml) and from the same dilutions spiked into fresh ovine EDTA-blood and spleen homogenate. The method showed a good degree of linearity (R2 ≥ 0.995). The limit of detection (LoD) and the limit of quantification (LoQ) established were 10−0.67TCID50/ml (0.72 copies/μl) and 100.03TCID50/ml (3.05 copies/μl) of BTV-1, respectively. Second, the newly developed test was compared, using the same set of biological samples, to the quantitative RT-PCR (RT-qPCR) detecting Seg-10 assay widely used for the molecular diagnosis of BTV from field samples. Results showed a difference mean of 0.30 log between the two assays with these samples (p < 0.05). Anyway, the analysis of correlation demonstrated that both assays provided similar measurements with a very close agreement between the systems.